2020
DOI: 10.1016/j.heliyon.2020.e03167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fiber orientation on the mechanical properties of multi layers laminate nanocomposites

Abstract: The effect of fiberglass type and adding a very small amount of Nano filler in the resin on mechanical and thermal properties of multilayers laminate composite has been studied. The results show clearly that laminate composites can be achieved by controlling the fiberglass type and by dispersing nanoparticles in the resin. Using continues fiber glass helps to increase the impact strength by 17 %-24% compared with samples with random fiberglass. The barcol hardness of continues fiberglass composite is 7% higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 39 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…A matrix holds all of the reinforcing fibers and agents together in a composite to transfer/share any external stress within the constituents for providing protection against any degradative processes, either in a mechanical (impact damage, delamination, high temperature, creep, and water absorption) or chemical form. The matrix is also termed a base material, and plays a critical role in composites carrying tensile loads in the structure [100,101]. There are four important matrix types: (1) metallic, (2) polymeric, (3) carbon, and (4) ceramic.…”
Section: Polymer/matrixmentioning
confidence: 99%
“…A matrix holds all of the reinforcing fibers and agents together in a composite to transfer/share any external stress within the constituents for providing protection against any degradative processes, either in a mechanical (impact damage, delamination, high temperature, creep, and water absorption) or chemical form. The matrix is also termed a base material, and plays a critical role in composites carrying tensile loads in the structure [100,101]. There are four important matrix types: (1) metallic, (2) polymeric, (3) carbon, and (4) ceramic.…”
Section: Polymer/matrixmentioning
confidence: 99%
“…Due to the low susceptibility to moisture, higher mechanical strength, reduced manufacturing cost, and improved electrical insulating properties, E-glass fibers are considered as a useful reinforcement to polymer composites as observed in the studies reported by Vijay Kumar and co-authors. [4] The studies of Amal Nassar and co-authors [5] have revealed the significance of hybrid fillers, which combines the good characteristics of both the micron-and nano-sized fillers. The principle of hybrid fillers is that the one filler can enhance the characteristics which are limited by the presence of the other filler due to synergistic effects.…”
Section: Introductionmentioning
confidence: 99%
“…In details, the decrement of GNP nanocomposites was recorded about 9%, 23%, 26%, 31%, and 49% for 0.2 wt%, 0.4 wt%, 0.6 wt%, 0.8 wt%, and 1.0 wt% loading of GNP, respectively. It is interesting to note that this result showed a little variation as compared to the previous research of epoxy resin/GNP nanocomposites which reported the increase in impact strength for low GNP loading and further decrement for higher GNP (~0.5 wt% and above 3,15 ) loading. As reported in the literature, the increase in impact strength can be explained by the micro‐plastic deformation occurring around the GNP 7 .…”
Section: Resultsmentioning
confidence: 40%
“…Numerous studies have been carried on pure epoxy resin reinforced with raw 6,7,15,16 or modified GNP 3,17 in the range of 0.1–3 wt%. Despite of these studies, the investigation of GNP reinforcement into the rubber‐modified epoxy was very few 8,14 .…”
Section: Introductionmentioning
confidence: 99%